Global survey of rice breeders to investigate characteristics and willingness to adopt alternative breeding methods - Lenaerts, Bert; Collard, Bertrand C. Y.; Demont, Matty (Springer, 2018)
Despite the critical role rice breeders play to ensure food security, there is a lack of information regarding their current socio-economic characteristics, constraints and attitudes towards technology adoption. Some key concepts like budget, experience, local ecosystems, level of education and even main breeding method have hardly been surveyed in the past. This not only clouds any policy making regarding scientists in national agricultural research programmes, it also makes it difficult to assess the needs and problems local rice breeders face around the world. A global online survey was conducted reaching 189 rice breeders from 51 rice-growing countries around the world. The questionnaire was structured according to an adoption framework we proposed from the literature. We specifically investigated their attitudes to adopting an alternative breeding method called rapid generation advance (RGA) (also known as single seed descent). To provide some historical perspective, we compare our results with those reported by Hargrove (Rice breeders in Asia: a ten-country survey of their backgrounds, attitudes, and use of genetic materials, 1978), the only published survey on rice breeders. Overall, rice breeders are highly educated and have a long experience with their main breeding method. However, a gender gap with respect to education seems to persist. Large variation in resources (staff, land and budget) was observed with a small number of resource-rich institutes and a large number of resource-poor institutes. Most rice breeders are focused on breeding for irrigated conditions. Most breeders have a relatively high degree of risk taking and time preference towards shorter breeding cycles. The majority of breeders are aware of RGA and its benefits with more than half having observed RGA in practice. Finally, breeders are confident in the RGA technique and estimate its resource savings to be substantial. Breeders’ willingness to adopt RGA was remarkably high. Surprisingly, adoption of RGA remains low (4% as main method). This may suggest that the benefits of using the RGA method still need to be further demonstrated in rice breeding. Our results could be useful to develop targeted extension material or interventions for implementing new technologies, which could be useful to high-level agricultural managers, international research centres and aid agencies.